2021
DOI: 10.1093/aobpla/plab027
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Xylella fastidiosa and functional xylem anatomy in Olea europaea: revisiting a tale of plant–pathogen interaction

Abstract: Background Xylella fastidiosa is a xylem-limited bacterium causing the Olive Quick Decline Syndrome, which is currently devastating the agricultural landscape of Southern Italy. The bacterium is injected into the xylem vessels of leaf petioles after the penetration of the insect vector’s stylet. From here, it is supposed to colonize the xylem vasculature moving against water flow inside conductive vessels. Widespread vessel clogging following the bacterial infection and causing the failure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 52 publications
8
36
0
Order By: Relevance
“…Similarly, studies suggest xylem vessel diameters probably play a role in the resistance of olive cultivar Leccino (Petit et al, 2021;Sabella et al, 2019). In particular, smaller diameter vessels are reported in Leccino in comparison with plants of susceptible cultivar Cellina di Nardò (Petit et al, 2021;Sabella et al, 2019). Moreover, Sabella et al (2019) made some general hypotheses as to how narrow vessels could be acting as a resistance mechanism in Leccino.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, studies suggest xylem vessel diameters probably play a role in the resistance of olive cultivar Leccino (Petit et al, 2021;Sabella et al, 2019). In particular, smaller diameter vessels are reported in Leccino in comparison with plants of susceptible cultivar Cellina di Nardò (Petit et al, 2021;Sabella et al, 2019). Moreover, Sabella et al (2019) made some general hypotheses as to how narrow vessels could be acting as a resistance mechanism in Leccino.…”
Section: Introductionmentioning
confidence: 93%
“…Previous reports have indicated that the bacteria can cause an increase in pit permeability (increased size and diameter) through the action of a battery of CWDEs that degrade the polysaccharide components of the middle lamella, thus enlarging the pore diameter and allowing systemic colonization (Fanton & Brodersen, 2021; Ingel et al, 2019). A side effect of this degradation is an increased risk of embolism, which leads to the disruption of water transport; such an effect is exacerbated in the susceptible olive cultivar Cellina di Nardò, which has a higher air‐embolism vulnerability than the resistant Leccino because of the larger lumen of its xylem vessels (Petit et al, 2021). While we did not prove the direct involvement of CWDEs in olive infections, our observations clearly indicate that XfDD enlarges PMs of susceptible cultivars to spread systemically.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of X. fastidiosa, Gram-negative bacteria that specialize in the colonization of xylem vessels, the primary infection happens through insect vectors feeding on the plant. The plant responds by secreting gels and creating tyloses, limiting the spread of the bacteria (Petit et al, 2021).…”
Section: Wilt Pathogens and Their Impact On Xylemmentioning
confidence: 99%
“…In the case of X. fastidiosa , Gram‐negative bacteria that specialize in the colonization of xylem vessels, the primary infection happens through insect vectors feeding on the plant. The plant responds by secreting gels and creating tyloses, limiting the spread of the bacteria (Petit et al, 2021 ). In a recent study on olive trees, the authors compared the xylem anatomy in two cultivars with different susceptibility to Xylella f. Interestingly, they found that the highly susceptible cultivar had larger xylem vessels and higher air‐embolism vulnerability that possibly facilitate the infection (Petit et al, 2021 ).…”
Section: Wilt Pathogens and Their Impact On Xylemmentioning
confidence: 99%
See 1 more Smart Citation